Labour market institutions and unemployment: An international comparison - Gebhard Flaig; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper deals with the effects of labour market institutions on unemployment in a panel of 19 OECD countries for the period 1960 to 2000. In contrast to many other studies, we use long time series and analyze cyclically adjusted trend values of the unemployment rate. Our novel contribution is the estimation of panel models where we allow for heterogeneous effects of institutions on unemployment. Our main results are that on the average a tighter employment protection, a higher tax burden on labour income and a more generous unemployment insurance system increase, whereas a higher centralization of wage negotiations decreases unemployment. The strength of the effects differs considerably between countries.
Keywords: J23; E24; J50; 330; employment protection; labour market institutions; unemployment; international comparison; Arbeitslosigkeit; Arbeitsmarktflexibilität; Arbeitnehmerschutz; Institutionelle Infrastruktur; Vergleich; Schätzung; OECD-Staaten